Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/biom11020199
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress and Unfolded Protein Response in Leukemia: Friend, Foe, or Both?

Abstract: The unfolded protein response (UPR) is an evolutionarily conserved adaptive signaling pathway triggered by a stress of the endoplasmic reticulum (ER) lumen compartment, which is initiated by the accumulation of unfolded proteins. This response, mediated by three sensors-Inositol Requiring Enzyme 1 (IRE1), Activating Transcription Factor 6 (ATF6), and Protein Kinase RNA-Like Endoplasmic Reticulum Kinase (PERK)—allows restoring protein homeostasis and maintaining cell survival. UPR represents a major cytoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 258 publications
(199 reference statements)
0
32
0
Order By: Relevance
“…Therefore, its increase in cellular levels is related to both cell survival and death, as its transcription is amplified in an attempt to normalize protein synthesis, prevented by the PERK pathway. The reversal of the inhibition of the translation process leads not only to the production of apoptotic proteins, but also to those related to cell continuity (Ma and Hendershot, 2003;Adams et al, 2019;Féral et al, 2021). The activation of this pathway reinforces the importance of proteasome inhibitors as an interesting option for cancer therapy.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, its increase in cellular levels is related to both cell survival and death, as its transcription is amplified in an attempt to normalize protein synthesis, prevented by the PERK pathway. The reversal of the inhibition of the translation process leads not only to the production of apoptotic proteins, but also to those related to cell continuity (Ma and Hendershot, 2003;Adams et al, 2019;Féral et al, 2021). The activation of this pathway reinforces the importance of proteasome inhibitors as an interesting option for cancer therapy.…”
Section: Discussionmentioning
confidence: 83%
“…Accordingly, eIF-2α hyperphosphorylation in response to environmental stress or drug exposure reduces global translation [ 37 ]. Of note, previous studies have demonstrated the CX-4945-induced eIF-2α hyperphosphorylation in eye cells [ 38 ] and leukemia cells [ 39 ]. In agreement with this, we have shown the capability of CX-4945 to elevate the phosphorylation of eIF-2α in HuCCT-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These vesicles transfer different bioactive molecules such as proteins, lipids, DNA and RNA. Since hypoxia, nutrients deprivation and acidosis render bone marrow an extremely hostile environment even for leukemic blasts, they cope with ER stress conditions by activating the unfolded protein response (UPR) [ 53 ] and it was shown that AML extracellular vesicles (AML-EVs) transfer ER stress to bone marrow mesenchymal stem cells, thus creating a leukemia permissive microenvironment [ 54 ]. Ultimately, the anchorage of leukemic stem cells to the niche also plays an essential role in AML pathogenesis [ 55 , 56 ].…”
Section: Aml and The Leukemic Bm Nichementioning
confidence: 99%